The Influence of International Crude Oil Price, Fuel Consumption and Production on Fuel Import (A Case Study at PT Pertamina (Persero)) - Ajeng Najla Fadhilah; Riyadi - Riyadi; Erika - Devie (Politeknik Negeri Semarang, 2020)
The purposes of this study were to analyze the influence of International Crude Oil Price Fuel Consumption and Production on Fuel Import and to find out how many contributions of all independent variables to dependent variable. Multiple Linear Regression Analysis method was used in this study. Data used in this study were secondary data collected from PT Pertamina (Persero) and summarized by Ministry of Energy and Mineral Resource (period 2005 -2016). The result of F-test showed that simultaneously and significantly all of independent variables influenced dependent variable. Meanwhile, t-test result showed that only Fuel Consumption had a significant influence on Fuel Import. However, the other independent variables did not have partial influence on Fuel Import. While, based on coefficient of determination test, it was found that International Crude Oil Price, Fuel Consumption and Production had a high contribution in explaining fuel import. In addition,the interpretation model showed positive equation of Fuel Consumption, so it means that if there is an increase in Fuel Consumption then Fuel Import will also increase.